Stacey and the mystery money - Martin, Ann M., 1955-; Scholastic Inc. (New York : Scholastic, 1993)
Counterfeit money is showing up in Stoneybrook and someone gave Stacey a fake ten dollar bill. The Baby-sitters want to discover where the money is coming from.
"An Apple paperback.".
5.3
3-6
Keywords: Babysitting -- Fiction; Counterfeits and counterfeiting -- Fiction; Mystery and detective stories; Babysitting -- Fiction; Counterfeits and counterfeiting -- Fiction; Mystery fiction